(untitled) (Medico Legal Update, 2021)
Aim of Study: Study the level of IL17 and IL23 in the follicular fluid and their relation with hyper stimulation syndrome. Materials/Method: Eighty five who include (85 subject divided into 2 groups, control group whom included infertile female with male factor infertility (55) and case group whom infertility due to poly cystic ovarian syndrome (30) attended IVF centre. Samples collected were follicular fluid, the follicular fluid has been collected in Eppendorf tube then stored at -20c to be used for ELISA test to determine concentration of IL 23 and IL 17 in follicular fluid. The results were analyzed using the IBM SPSS analytic software. Results: the mean of interleukin (IL17) 96.11, Standard deviation 78.46 in the patients group. While the mean of interleukin (IL 17) for control 6.15, Standard deviation 14.33. There was a significant difference between polycystic and male factor infertility. P value < 0.005 both of them groups Poly cystic and male factor. Conclusions: High concentration of follicular fluid IL -17 is positively associated with e disease of poly cystic ovary (POCS).